Multispectral Enhancement towards Digital Staining - Pinky A. Bautista; Yukako Yagi (Analytical Cellular Pathology, 2012)
Background: Digital staining can be considered as a special form of image enhancement wherein the concern is not only to increase the contrast between the background objects and objects of interest, but to also impart the colors that mark the objects’ unique reactions to a specific stain. In this paper, we extended the previously proposed multispectral enhancement methods such that the colors of the background pixels can also be changed.